Effect of trans-zeatin riboside application on growth of banana (Musa AAA Simmonds) cv. Williams in the juvenile phase - Schiller, Luis Gregorio; Magnitskiy, Stanislav (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Cytokinins are physiologically active adenine derivatives that are vital to the regulation of various developmental processes in plants, such as vegetative growth and flower induction. The objective of this study was to understand how the application of cytokinin trans-zeatin riboside affects growth in banana (Musa AAA Simmonds) cv. Williams plants during the vegetative phase on two farms located in the production zone of the Magdalena province, Colombia. The effect of trans-zeatin riboside applications at doses of 0.00, 0.05, 0.25, or 0.45 mg L-1 via foliar spraying was evaluated, with 15 days between the applications, starting with transplant to the field and lasting until 10 weeks of growth. The treatment 0.05 mg L-1 of cytokinin resulted in increases in the plant growth variables, such as height in V, pseudostem diameter, leaf width, and leaf area.